The library game - Pandian, Gigi, 1975- (Pandian, Gigi, 1975- Secret staircase mystery, 2025)
"In The Library Game, Tempest Raj and Secret Staircase Construction are renovating a classic detective fiction library that just got its first real-life mystery. Tempest Raj couldn't be happier that the family business, Secret Staircase Construction, is finally getting the recognition it deserves. Known for enchanting architectural features like sliding bookshelves and secret passageways, the company is now taking on a dream project: transforming a home into a public library that celebrates history's greatest fictional detectives. Though the work is far from done, Gray House Library's new owner is eager to host a murder mystery dinner and literary themed escape room. But when a rehearsal ends with an actor murdered and the body vanishes, Tempest is witness to a seemingly impossible crime. Fueled by her grandfather's Scottish and Indian meals, Tempest and the rest of the crew must figure out who is making beloved classic mystery plots come to life in a deadly game. Multiple award winning author Gigi Pandian masterfully weaves wit and warmth in the Secret Staircase Mysteries. Readers will delight in the surprises Secret Staircase Construction uncovers behind the next locked door"--